Aquatic versus land-based exercise for cardiorespiratory endurance and quality of life in obese patients with knee osteoarthritis: a randomized controlled trial (Medical Journal of Indonesia, 2018)
Background: Obesity with knee osteoarthritis (OA) is related to chronic pain causing physical inactivity that leads to decreased cardiorespiratory endurance and quality of life. Aquatic and land-based exercises are effective in improving physical activity. The aim of this study is to compare between aquatic and land-based exercise to improve cardiorespiratory endurance and quality of life in obese patients with knee osteoarthritis.Methods: A single-blind, randomized, controlled trial was conducted on thirty three obese patients with knee OA who visited Obesity Clinic of Medical Rehabilitation Cipto Mangunkusumo Hospital, from October 2016 to January 2017, subjects were divided into aquatic or land-based exercise group. Aerobic and knee-strengthening exercises were given. Cardiorespiratory endurance was assessed using the Borg Scale, whereas both the BORG CR-10 and SF-36 questionnaires were used to assess quality of life.Results: After intervention, there were significant improvements in the land-based exercise group in the rating of perceived exertion (p=0.02), role limitations due to physical health (p=0.024), role limitations due to emotional problems (p=0.041), energy/fatigue (p=0.016), and the decline in pain (p=0.049) parameters. While in the aquatic exercise, there were significant improvements in leg fatigue (p=0.016), energy/fatigue (p=0.025), emotional well-being (p<0.001), and general health (p=0.045) parameters. Despite this, there were no significant differences between two groups regarding cardiorespiratory endurance and quality of life.Conclusion: This study found that patients could start aquatic exercise to reduce leg fatigue and enhanced general health and energy. After that, exercise could be continued in land-based settings to improve cardiorespiratory endurance and quality of life.